Preimaginal stages of Triplectides misionensis Holzenthal and Triplectides gracilis (Burmeister) (Trichoptera: Leptoceridae: Triplectidinae), with notes on the cases occupied by these species - Sganga, Julieta V.; Angrisano, Elisa B.; Asaroff, Pablo E. (Zootaxa, 2013)
The larvae, pupae and cases of Triplectides misionensis Holzenthal and T. gracilis (Burmeister) are described from spec-imens collected in protected areas from northeastern Argentina. The larvae are easily differentiated by the coloration of the cephalic capsule, shape of the ventral apotome and submentum, anterior border of the pronotum, and coloration of the legs, among other characters, while the pupae can be recognized by the chaetotaxy of the head. The larvae occupy empty cases of Grumicha grumicha Valot and Nectopsyche gemma (Müller), as well as hollow twigs. Triplectides misionensis is found almost exclusively in cases of G. grumicha while T. gracilis prefers twigs of different sizes.